Fantasy Formula in the Story of the Nusantara Webtoon Droid War by Vega Mandalika - Moh. Daffa Nugraha; Dina Nurmalisa; Rana Sharjeel Akhtar; Emmanuel Ofori Gyadu (Universitas Negeri Semarang, 2025)
Webtoon NDW is a literary work that presents vertical image panels, making it unique from other scholarly works. As a popular fantasy genre work, researchers suspect that there is a formula in the Webtoon NDW story. This study aims to reveal the fantasy formula in the Webtoon Nusantara Droid War (NDW) story by Vega Mandalika. The type of research is qualitative and uses the theoretical basis of the fantasy formula from Deborah Chester (2016), which consists of three elements: story roles, magic, and a special world. Data were obtained from episodes 1 to 50 of Webtoon NDW through data collection with documentation techniques and literature studies. Then, it was analyzed through data condensation, presentation, and conclusion to find patterns in the research object. The study results show that the Webtoon NDW story has three categories of characters, each with its role. The closer a character is to the minor category, the more limited their appearance will be. The story's characters use spells with different functions, such as turning on droids or summoning magical powers. Webtoon NDW presents a special world with wonders not found in other worlds. These three elements are present repeatedly and consistently in the Webtoon NDW story. Thus, some patterns in the NDW story follow the fantasy formula proposed by Deborah Chester. The study results help develop popular literary theory, especially the fantasy formula in Webtoon, and serve as a reference for similar research in the future. This study requires further research to determine the influence and effectiveness of Webtoon NDW in learning literature in the digital era.